스마트 농업의 작물 생존 예측을 위한 인공지능 분석 - 노미진(Mi Jin Noh) (스마트미디어저널, 2025)
Smart agriculture has been evolving by integrating ICT, IoT, and AI technologies to maximize agricultural productivity and optimize resource utilization. This study aims to predict crop survival in smart agriculture using various machine learning and deep learning models while analyzing and comparing their performance. To achieve this, Random Forest, XGBoost, LightGBM, LSTM, and GRU models were implemented, and their predictive performance was evaluated using accuracy, precision, recall, and F1-score. SHAP analysis was applied to enhance model interpretability and assess the impact of key variables on prediction outcomes. The experimental results indicate that XGBoost and LightGBM demonstrate the highest predictive performance, confirming the effectiveness of tree-based boosting models in crop survival prediction. Notably, SHAP analysis reveals that variables such as pesticide usage type, estimated insect count, and pesticide application frequency significantly influence the prediction results. This study highlights the potential of AI-based predictive models in smart agriculture and emphasizes the importance of optimizing controllable environmental factors to improve crop survival rates. 스마트 농업은 ICT, IoT, AI 기술을 활용하여 농업 생산성을 극대화하고 자원의 효율적 사용을 도모하는 방향으로 발전하고 있다. 본 연구는 다양한 머신러닝 및 딥러닝 모델을 활용하여 스마트 농업에서 작물 생존 예측을 수행하고, 모델 간 성능을 비교 및 분석하는 것이다. 이를 위해 랜덤포레스트, XGBoost, LightGBM, LSTM, GRU 모델을 적용하여 예측 성능을 평가하고, 정확도, 정밀도, 재현율, F1-score 지표를 활용해 비교 분석을 수행하였다. 모델의 해석 가능성을 높이기 위해 SHAP 분석을 적용하여 주요 변수들이 예측 결과에 미치는 영향을 분석하였다. 분석 결과, XGBoost와 Light GBM이 가장 높은 예측 성능을 보였으며, 트리 기반 부스팅 모델이 작물 생존 예측에 효과적임을 확인하였다. SHAP 분석을 통해 살충제 사용 유형, 추정 곤충수, 살충제 사용 주기 등의 변수가 예측 결과에 중요한 영향을 미치는 것으로 나타났다. 본 연구는 스마트 농업에서 인공지능 기반 예측 모델의 활용 가능성을 제시하며, 농부가 직접 조절할 수 있는 환경적 요소의 최적화가 작물 생존율 향상에 중요한 역할을 할 수 있음을 시사한다.